Uwarunkowania bezpieczeństwa Czarnogóry .......... 201 - Łakota-Micker, Małgorzata (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
The term ‘security’ is one of the key categories for functioning of the state and the state of international relations as presented in the literature on the subject. Today, internal conflicts and inner crisis remain a frequent threat to national security. The region that has significantly experienced these threats is the Western Balkans. European Union gave this area special attention in the year of 2018. Established as a result of the breakup with Serbia in 2006, Montenegro aspires for EU membership. Ruled by pro-European president Milo Djukanović, Montenegro managed to join NATO in 2017 and negotiates accession within the EU. Seemingly successful and effective path for development of a relatively young country, in fact brings many different problems and internal tensions. Those can affect the security of Montenegro with threats.